Cathodic electrogenerated chemiluminescence of luminol on glassy carbon electrode modified with cobalt nanoparticles decorated multi-walled carbon nanotubes. (1st February 2015) - Haghighi, Behzad; Tavakoli, Azam; Bozorgzadeh, Somayyeh
Graphical abstract: Highlights: GCE was modified with Co nanoparticles decorated MWCNTs. Modified GCE showed sensitizing effect on reactive oxygen species production. Modified GCE was applied for cathodic ECL determination of luminol and oxygen. The reaction between ROSs and deprotonated form of luminol produced ECL signal. Abstract: Cobalt nanoparticles with a typical size of 5 nm were decorated on multi-walled carbon nanotubes by the use of a simple, rapid, solvent less thermal decomposition method. The cathodic electrogenerated chemiluminescence (ECL) behavior of luminol was investigated on a glassy carbon electrode modified with cobalt nanoparticles decorated multi-walled carbon nanotubes. The prepared sensor exhibited excellent electrocatalytic activity towards production of reactive oxygen species (ROSs) and consequently oxygen reduction reaction. Sweep of potential in cathodic direction produced an ECL signal at the potential about -0.5 V versus Ag|AgCl|KClsat due to the reaction between deprotonated form of luminol and ROSs. The produced cathodic ECL signal intensity was linear towards luminol in the concentration range between 5 and 770 μM (r = 0.9984) with a detection limit of 110 nM. Also, under optimal conditions, the ECL signal intensity of luminol was linear towards dissolved O2 in the concentration range between 0.08 and 0.94 mM (r = 0.9914) with a detection limit of 0.04 mM. The relative standard deviations (RSD) for repetitive measurements of 20 μM luminol (n = 10) and 0.50 mM oxygen (n = 10) at pH = 9.0 were of 3.0 and 3.9%, respectively. A possible mechanism for cathodic ECL reaction of luminol has been discussed.